The Potential Impact of Japanese Nuclear Waste on Fish Organs in the Sea of Japan - Lathifatun Nikmatil Aula; Aditya Putri Ristanti; Novianah Khalimatus Sa`diyah; Ibrahim bin Sa’id (Jurnal Agricultural Science, 2023)
The purpose of this research is to assess the environmental impact of nuclear waste disposal and understand the applicable laws in countries engaging in nuclear waste disposal, in accordance with international environmental law stipulated in international conventions. The author conducted this research using a literature review method and a qualitative approach. From the study, it can be concluded that if Japan's government decision to discharge radioactive water into the Pacific Ocean causes marine pollution, Japan may be held accountable for violating international law.